Delay-Dependent Robust Exponential Stability and H∞ Analysis for a Class of Uncertain Markovian Jumping System with Multiple Delays - Jianwei Xia (Abstract and Applied Analysis)
This paper deals with the problem of robust exponential stability and H∞ performance analysis for a class of uncertain Markovian jumping system with multiple delays. Based on the reciprocally convex approach, some novel delay-dependent stability criteria for the addressed system are derived. At last, numerical examples is given presented to show the effectiveness of the proposed results.